A produção acadêmica brasileira sobre o ensino médio privado: balanço tendencial das dissertações e teses - Silva, André Luiz Rebelo da (2017)
The discussion about the purpose of secondary education, as well as its social function, is as old as the very existence of this segment as an integral part of what is now called basic education. In the context of its commitment to the student learning process, there has always been a duality related to the propaedeutic high school and the vocational high school. The history of education, however, reveals another face of this schooling phase, concerning to the market opportunities that the private initiative found in the exploitation of this level of education. This research intends to carry out an analysis on the type of productions which have been made by the postgraduate programs about private secondary education. It is a bibliographical research of quantitative-qualitative nature, which analyzes data from the abstracts available in the bank of thesis pertaining to CAPES (Coordination of Improvement of Higher Education Personnel),within the period of 2013-2016.It refers to 121 productions about high school education in Brazil, and aims at answering questions concerning to who, when, where and how has studied the Brazilian secondary education through academic productions. Analysis have been theoretically supported by the contributions of cultural materialism (Williams, 1980), through which particularities of material production to understand socio-historical practices have been verified. It is concluded that, among other factors, there is little interest in private secondary education as an object of research. Most of the academic productions are predominantly concentrated in the São Paulo State by education and teaching programs, and their studies prioritize the thematic fields of teaching and pedagogical practices